Testicular alterations and semen quality in a selected group of breeding buffaloes - Albuquerque, Rodrigo Dos Santos; Monteiro, Francisco Décio de Oliveira; Lima, Moises Moreira; da SILVA, Aluizio Otavio Almeida; E Cunha, Michel Santos; da CONCEIÇÃO, Maria Eduarda Bastos Andrade Moutinho; Scheeren, Verônica Flores da Cunha [UNESP]; Freitas, Camila de Paula [UNESP]; Papa, Frederico Ozanam [UNESP]; Monteiro, Bruno Moura; Viana, Rinaldo Batista; Coutinho, Leandro Nassar; et al. (Japanese Society of Veterinary Science, 2023)
Testicular ultrasound enables the evaluation of changes in the testicular parenchyma. This study aimed to report the occurrence of hypoechogenic testicular alterations and their relationship with semen quality in five breeding buffaloes. Two buffaloes presented with hyperechoic points characteristic of fibrosis and anechoic density content between the parietal and visceral tunica. The two bulls without ultrasonographic changes showed higher average trajectory speed, linear velocity, curvilinear velocity, amplitude of lateral displacement of the spermatic head, total motility, progressive motility, fast speed, and acrosomal membrane values within the normal range. The number of spermatozoa with major and total defects was higher in the group of animals without alterations. The three buffaloes that presented with testicular alterations produced semen within established freezing standards.
Keywords: andrology; bull; echogenicity; testicular fibrosis; ultrasound dopple